AJIC Issue 26, 2020 - Full Issue - print-on-demand version - (:unkn) unknown (My University, 2020)
Thematic Issue: Collaborative Innovation in African Settings: Articles on artificial intelligence, Indigenous data sovereignty, mobile tech start-ups, tech hubs, makerspaces, and social entrepreneurs.